Tuberculosis Related Attitude and Stigma Among Pregnant Women in Orumba South Local Government Area, Anambra State - Obi, Ifunanya R; Samuel, Effiong Sunday; Obi, Kamtoochukwu M. (International Journal of Human Kinetics, Health and Education, 2023)
The purpose of the study was to find out the tuberculosis (TB) related attitude and stigma among pregnant women attending antenatal clinics in Primary Health Care centres in the rural communities in Orumba South Local Government Area of Anambra State. To achieve the purpose of the study, two objectives were formulated with two corresponding research questions while four hypotheses were postulated. The cross-sectional research design was used for the study. The population for this study consisted of all the pregnant women attending antenatal clinics in the eleven PHCs and convenience sampling technique was used to draw a sample of 260 pregnant women used for the study. The instrument for data collection was a questionnaire. Frequencies and percentages were used to answer research questions, while Chi-square statistic was used for testing the null hypotheses. The result of the study indicated that: majority (65.33%) of pregnant women had positive attitude towards TB and slightly less than one-half of pregnant women demonstrated TB related stigma, there was no significant difference in TB related attitude by pregnant women according to age (χ2 = 4.687, p= .292 > .05) and level of education (χ2 = 13.324, p= .382 > .05). There was no significant difference in TB related stigma according to age (χ2 = 2.196, p= .138> .05)while there was significant difference in TB related stigma by pregnant women according to level of education (χ2 = 11.286, p= .010 < .05). Based on major findings and conclusions, it was recommended among others that government and non-governmental organizations should develop suitable intervention programmes that will convince pregnant women and members of the community to have zero TB related stigma through effective health education in the communities.